Historical aspects of the development of public-private partnership in the countries of the world and Ukraine. Feasibility of using PPP mechanisms to optimize secondary outpatient - Kravchenko, V. V. (Journal of Education, Health and Sport, 2017)
Introduction. Today, in the face of failure of funding and absence of a radical change in the country, the current situation is ineffective health care system. The need for solving these tasks made necessary the development of complex of measures that go beyond the competences and financial capabilities of the State and share sectors, which allowed to establish the Institute for public-private cooperation. Objective: to study historical aspects of development of private partnership in the countries of the world and Ukraine. the feasibility of using PPP mechanisms to optimize secondary outpatient care. Materials and methods: the research performed using the method of the system approach and analysis. Information Base for its implementation have become scientific papers of foreign dealers. The results of the study. The research found that in the world formed the successful experience of wide use and high level of development of mechanisms for public-private partnerships. The transition to using PPP mechanisms in the system of secondary outpatient care, in particular, in the Organization of work of the consultative-diagnostic centers, will greatly improve the situation through the use of additional investment, optimize costs and creation of conditions for technological leapfrogging and sustainable development of CDC, will create conditions for efficient address use of resources, improving the accessibility and quality of care to the population.